Music Therapists’ Experiences of Providing Telehealth Music Therapy for People with Dementia - Lisa Kelly; Hilary Moss; Ita Richardson (Voices)
Due to the impact of COVID-19, music therapy practice rapidly transitioned from the traditional in-person format to an online context. Despite the return of in-person services, telehealth music therapy has the potential to support people with dementia who do not have access to or are no longer able to attend in-person services. This qualitative exploration aims to contribute to the emerging literature on telehealth music therapy for people with dementia, providing practical recommendations for practice. Semi-structured interviews were conducted with four senior music therapists who provided telehealth music therapy for people with dementia during and after the COVID-19 pandemic. Telehealth music therapy appears to be a viable alternative to in-person music therapy, particularly for those people at the end stages of dementia, who have physical limitations, who have unreliable access to transport, or who are socially isolated. It is particularly appropriate for those who live in rural areas where access to community supports is limited. The delivery of music therapy via telehealth allows music therapists to continue to support people with dementia and their family from the comfort of their own homes when access to community-based services is no longer feasible. Barriers such as digital literacy, access to technology, and caregiver support must be acknowledged. Findings from this study indicate that a therapeutic relationship can be both established and maintained through music via telehealth music therapy.